2015
DOI: 10.1002/mop.28906
|View full text |Cite
|
Sign up to set email alerts
|

Frequency reconfigurable dielectric resonator antenna for WiMAX/WLAN applications

Abstract: A CPW‐fed frequency reconfigurable dielectric resonator antenna (DRA) is studied and presented for WiMAX and wireless local area network applications. The frequency tunable DRA is able to alter the frequency at three different dual bands frequency. The rectangular dielectric resonator has a permittivity of 10. Two PIN diode switches are located on the connecting lines of the network, which feeds the three dielectric resonator elements. Three dual‐band modes with center frequency of 2.4 and 5 GHz in ON–ON state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Danish et al (2015) also reported a 33 Â 45 mm 2 frequency agile array composed of three RDRs. 15 Two PIN diodes were used as switches to obtain three dual-band resonance modes, that is, 2.4 and 5 GHz mode, 2.5 and 5.2 GHz mode, and 3.5 and 5.8 GHz mode. Again, the realized gain was small which ranged from 1.17 to 2.14 dBi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Danish et al (2015) also reported a 33 Â 45 mm 2 frequency agile array composed of three RDRs. 15 Two PIN diodes were used as switches to obtain three dual-band resonance modes, that is, 2.4 and 5 GHz mode, 2.5 and 5.2 GHz mode, and 3.5 and 5.8 GHz mode. Again, the realized gain was small which ranged from 1.17 to 2.14 dBi.…”
Section: Introductionmentioning
confidence: 99%
“…However, the gain was small ranging from 1.78 to 2.61 dBi. Danish et al (2015) also reported a 33 × 45 mm 2 frequency agile array composed of three RDRs 15 . Two PIN diodes were used as switches to obtain three dual‐band resonance modes, that is, 2.4 and 5 GHz mode, 2.5 and 5.2 GHz mode, and 3.5 and 5.8 GHz mode.…”
Section: Introductionmentioning
confidence: 99%
“…In [17], a CPW-fed frequency tunable RDRA using two diodes is presented that changes from narrow-band to wide-band with the change in diode operation. A three RDR integrated with two PIN diodes produces dual-band frequency-reconfigurability in one/both ON-states [18]. Similarly, three diodes integrated among four RDRs works only for two/more ON-states to achieve a single-band frequencyreconfigurability [19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, three diodes integrated among four RDRs works only for two/more ON-states to achieve a single-band frequencyreconfigurability [19]. The increased number of elements and associated bias lines in [18], [19] results in com- plexity. In [20], a combination of three diodes achieved a narrow-band tunable response.…”
Section: Introductionmentioning
confidence: 99%
“…This reconfigurable dielectric resonator antenna works in different bands by setting the switch on the connecting lines of a network that feeds the dielectric element and changing the state of switch from ON to OFF, a shift of the well-matched operating frequency range is obtained. In [25] an air-filled channel between dielectric resonator antenna and the plane of the ground is introduced, which can lead a frequency shift to lower frequencies by employing a slide metalized dielectric slugs under the DR. Another technique that brings about a reconfigurable DRA is the use of the switches on the way of feed line to create some dual-band and narrowband frequency [26], [27]. However, by using different types of electronic devices such as field-effect transistors (FETs), microelectromechanical system switches (MEMS), or PIN diodes can attain discrete tunable frequency [28], [29].…”
Section: Introductionmentioning
confidence: 99%